2023
DOI: 10.3127/ajis.v27i0.3985
|View full text |Cite
|
Sign up to set email alerts
|

How Big Five Personality Traits affect Information and Communication Technology Use: A Meta-Analysis

Abstract: This study performed a meta-analysis of forty-eight studies to synthesize existing literature examining the relationship between ‘Big Five’ personality traits and the use of various Information and Communication Technologies (ICTs). We conducted sub-group analysis to investigate the potential moderators on the relationship between personality and ICT use. The results largely reveal that the ‘Big Five’ personality traits are significantly associated with the use of various ICTs. Specifically, ‘extroversion’ sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 108 publications
(196 reference statements)
0
2
0
1
Order By: Relevance
“…In another recent study, a meta-analysis examining general social media use, Extroversion and Openness were significantly and consistently related to the use of such platforms [157]. Internet addiction, on the other hand, correlates with different personality profiles; Neuroticism has been shown to be positively correlated with internet addiction, whereas Openness, Agreeableness, and Conscientiousness are negatively correlated [158].…”
Section: Neurological Appreciation Of Beauty: Insights From the Five-...mentioning
confidence: 95%
“…In another recent study, a meta-analysis examining general social media use, Extroversion and Openness were significantly and consistently related to the use of such platforms [157]. Internet addiction, on the other hand, correlates with different personality profiles; Neuroticism has been shown to be positively correlated with internet addiction, whereas Openness, Agreeableness, and Conscientiousness are negatively correlated [158].…”
Section: Neurological Appreciation Of Beauty: Insights From the Five-...mentioning
confidence: 95%
“…Pertama, perkembangan teknologi komunikasi yang semakin canggih dan terjangkau memberikan kontribusi besar dengan memungkinkan akses lebih mudah dan luas terhadap berbagai platform digital. Kecepatan dan kualitas konektivitas yang semakin baik turut mendukung masyarakat dalam menjelajahi dunia digital dengan lebih lancar (Joshi et al, 2023).…”
Section: Temuan Peningkatan Waktu Konsumsi Digital Mediaunclassified
“…Furthermore, scholars have found that personality can influence W_ICTs [ 52 ]. According to the Regulatory Focus Theory, employees with a prevention focus are more inclined to seek job security and stability [ 53 ].…”
Section: Introductionmentioning
confidence: 99%